Big Data-Artificial Intelligence as a Systemic Procedure in the Field of Legal and Forensic Medicine - Pérez, Elena Martín; Martín, Quintín Martín (Science and Technology: Developments and Applications Vol. 6, 2025)
The combination of Big Data (BD), Artificial Intelligence (AI) and Systemic Procedure (SP) constitutes a transversal technological approach focused on improving decision-making in the field of Medicine and, in particular, of Legal and Forensic Medicine. It is advisable that medical professionals become increasingly involved in the knowledge of new concepts, technologies and tools that are becoming increasingly essential for daily work. The terms Big Data and Artificial Intelligence are increasingly used, seeking a symbiosis between them. If we add to these terms the term Systemic Procedure, we have the necessary concepts to approach any field with greater efficiency. In recent years, Big Data in Medicine has become a phenomenon and the field of Legal and Forensic Medicine could not be left out. The complexity of the data processed in this field is evident and, therefore, requires special treatment. The application of Artificial Intelligence to forensic sciences is increasingly less questionable since reliable, verifiable and reproducible results are obtained. The characteristics (the V’s) with which Big Data is endowed are those that define it. The sequence of characteristics continues: 3, 5, 7, 9. We will focus on the development of Big Data through seven characteristics (7 V’s). The concepts (BD) and (AI) must go hand in hand with the growth of the greater computational capacity that is being developed and the improvement of the algorithms used. The objective of this article is to analyze, from a theoretical point of view, Big Data (BD) and Artificial Intelligence (AI) within the field of Legal and Forensic Medicine as a Systemic Procedure (SP) with a holistic perspective. Implementing Fig. 2 through algorithms of both Big Data and Artificial Intelligence with a Systemic Procedure structure will help decision-making in general and, in particular, in the field of Legal and Forensic Medicine.